Soft magnetic steel wire and method for producing the same
By reasonably formulating chemical components and controlling metal structures in soft magnetic wires, the problems of high deformation resistance and cracks in the cold forging process of existing soft magnetic wires at high processing speeds are solved, and the excellent magnetic properties and high processing performance of soft magnetic components are achieved.
Patent Information
- Application Number
- JP2023182804
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-24
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2043-10-24
AI Technical Summary
The existing soft magnetic steel wire has high deformation resistance and crack problems during the cold forging process at high processing speeds, making it difficult to meet the processing needs of complex-shaped components.
Use pure iron-based soft magnetic steel wires with specific chemical compositions, including C, Si, Mn, P, S and other elements to ensure that the area ratio of the ferrite phase region reaches 95.0% or more, the particle size is controlled at 7.0 or less, and the particle boundary content of ferrosilicon is controlled through heat treatment steps.
It realizes the low deformation resistance and crack-free cold forging performance of soft magnetic steel wire at high processing speed, and can produce soft magnetic parts with excellent magnetic properties.
Smart Images

Figure 2025072206000001 
Figure 2025072206000002 
Figure 2025072206000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a soft magnetic steel wire and a method for producing the same. [Background technology]
[0002] Soft magnetic steel has the characteristics of being easily magnetized by a weak external magnetic field and having a small coercive force. Taking advantage of these characteristics, soft magnetic steel is used as a material that constitutes magnetic circuits. Soft magnetic steel is mainly provided in the form of plate material, wire material, steel bar, etc., and is processed and magnetically annealed according to the application.
[0003] For example, Patent Document 1 discloses a soft magnetic steel material that can ensure stable and excellent magnetic properties after magnetic annealing and can be processed with good dimensional accuracy by cold forging. Patent Document 2 discloses a soft magnetic steel material that can ensure excellent magnetic properties with little variation after magnetic annealing, exhibits excellent machinability and cold forgeability in the manufacturing process, and can be used to manufacture large steel parts with complex shapes with high yields.
[0004] Another known application of soft magnetic steel material is, for example, a soft magnetic steel wire for ACSR (Aluminum Conductor Steel Reinforced) with low iron loss (e.g., Patent Document 3). ACSR steel wire is a strand of steel wire used to reinforce the Al conductor of a power transmission cable. The soft magnetic steel wire for ACSR disclosed in Patent Document 3 is a soft magnetic steel wire (pure iron-based soft magnetic steel wire) made of extremely low carbon steel with a C content of approximately 0.1 mass % or less, yet is said to be capable of achieving high strength (e.g., tensile strength exceeding 1000 MPa). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2007-238970 A [Patent Document 2] JP 2007-046125 A [Patent Document 3] Japanese Patent Application Publication No. 10-110245 Summary of the Invention [Problem to be solved by the invention]
[0006] Soft magnetic steel is used as a raw material for electrical components (especially electromagnetic components) in automobiles, etc. In one example, soft magnetic steel wire obtained by drawing soft magnetic wire or steel bar is processed by forging, cutting, etc. to form a component (soft magnetic component) of a desired shape. In recent years, there has been a trend for the shape of components to become more complex as automobiles become smaller and lighter, and cold forging is suitable for processing components of complex shapes.
[0007] Pure iron-based soft magnetic steel wire is very soft compared to other steels (such as carbon steels with a high carbon content) and is therefore suitable for cold forging. However, there is a demand for soft magnetic steel wire with better cold forging properties for use in manufacturing parts with complex shapes.
[0008] Although Patent Documents 1 and 2 disclose soft magnetic steel materials with improved cold forgeability, there is still a demand for soft magnetic steel wire with better cold forgeability, particularly soft magnetic steel wire that has low deformation resistance and does not crack when cold forging at a high processing ratio (e.g., a compression ratio of 90%).
[0009] The soft magnetic steel wire disclosed in Patent Document 3 is not intended to be processed by cold forging, and therefore cold forgeability is not taken into consideration. Since the soft magnetic steel wire in Patent Document 3 has high strength, it is expected to have high deformation resistance at a high processing rate, and is considered to have low cold forgeability.
[0010] Therefore, in one embodiment of the present invention, it is an object to provide a soft magnetic steel wire that is a pure iron-based soft magnetic steel wire that has excellent cold forgeability (particularly, low deformation resistance and no cracks even in cold forging at a high processing rate) and that can be used to manufacture soft magnetic parts with excellent magnetic properties by performing magnetic annealing after cold forging. In another embodiment of the present invention, it is an object to provide a method for manufacturing such a soft magnetic steel wire. [Means for solving the problem]
[0011] Aspect 1 of the present invention is C: more than 0% by mass, 0.025% by mass or less, Si: 0 mass% or more, 2.00 mass% or less, Mn: 0.10% by mass or more, 0.50% by mass or less, P: more than 0% by mass, 0.050% by mass or less, S: more than 0% by mass, 0.050% by mass or less, Cu: 0 mass% or more, 0.30 mass% or less, Ni: 0 mass% or more, 0.30 mass% or less, Cr: 0 mass% or more, 0.30 mass% or less, Mo: 0 mass% or more, 0.30 mass% or less, Al: 0 mass% or more, 0.030 mass% or less, Ti: 0 mass% or more, 0.030 mass% or less, Nb: 0 mass% or more, 0.030 mass% or less, V: 0 mass% or more, 0.030 mass% or less, B: 0 mass% or more, 0.0030 mass% or less, N: more than 0 mass% and 0.0100 mass% or less; The balance is Fe and unavoidable impurities, The area ratio of the ferrite phase is 95.0% or more. The grain size number of the ferrite phase is 7.0 or less, The soft magnetic steel wire has a grain boundary ratio of 6.8% or more, the grain boundary ratio including cementite having an equivalent circle diameter of 0.1 μm or more and 3 μm or less.
[0012] Aspect 2 of the present invention is The soft magnetic steel wire according to aspect 1, wherein the roundness R (mm) and the wire diameter D (mm) satisfy the following formula (1): R≦0.100-(20-D) / 500 (1)
[0013] Aspect 3 of the present invention is The soft magnetic steel wire according to aspect 2 further satisfies formula (2). R≦(0.100-(20-D) / 500)-0.035 (2)
[0014] A fourth aspect of the present invention is The soft magnetic steel wire according to any one of aspects 1 to 3, wherein in an X-ray diffraction pattern measured using Cr-Kα radiation as an X-ray source, the half-value width of a diffraction peak of a (211) plane of the ferrite phase is 1.75° or less.
[0015] A fifth aspect of the present invention is A method for producing a soft magnetic steel wire according to any one of aspects 1 to 4, comprising the steps of: A step of heating a cast material having the chemical composition described in embodiment 1 to 950 ° C. to 1250 ° C., hot rolling or hot forging at 900 ° C. to 1100 ° C., and then cooling to 500 ° C. at an average cooling rate of 0.1 ° C. / s to 10 ° C. / s to obtain a wire rod or a steel bar; A step of drawing the obtained wire rod or steel bar at a wire drawing reduction rate of 5 to 40%; The method for producing a soft magnetic steel wire includes, after the wire drawing process, a heat treatment process of holding the wire at a heat treatment temperature of 150°C or more and 500°C or less for 15 minutes or more and 10 hours or less. Effect of the Invention
[0016] According to one embodiment of the present invention, it is possible to provide a pure iron-based soft magnetic steel wire that has excellent cold forgeability and that can be used to manufacture soft magnetic parts having excellent magnetic properties by performing magnetic annealing after cold forging. According to another embodiment of the present invention, it is possible to provide a method for manufacturing such a soft magnetic steel wire. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present inventors have conducted extensive research to provide a pure iron-based soft magnetic steel wire that has excellent cold forgeability at a high processing rate and that can be used to manufacture soft magnetic parts having excellent magnetic properties by performing magnetic annealing after cold forging. As a result, they have found that it is important to control the metal structure of the soft magnetic steel wire, particularly the area ratio and grain size of the ferrite phase, and cementite at the grain boundaries. Based on this knowledge, the present inventors have completed a soft magnetic steel wire suitable for processing by cold forging.
[0018] In this specification, the term "steel wire" refers to a steel material that has been subjected to wire drawing (and heat treatment as necessary) after hot rolling. Pretreatment (e.g., pickling, lubricating coating treatment, etc.) may be performed before the wire drawing. The number of times wire drawing is performed during the wire drawing is not limited, and may be performed once or multiple times.
[0019] A soft magnetic steel wire and a manufacturing method thereof according to an embodiment of the present invention will be described in detail below.
[0020] 1.Chemical composition The soft magnetic steel wire according to the embodiment of the present invention has C: more than 0% by mass, 0.025% by mass or less, Si: 0 mass% or more, 2.00 mass% or less, Mn: 0.10% by mass or more, 0.50% by mass or less, P: more than 0% by mass, 0.050% by mass or less, S: more than 0% by mass, 0.050% by mass or less, Cu: 0 mass% or more, 0.30 mass% or less, Ni: 0 mass% or more, 0.30 mass% or less, Cr: 0 mass% or more, 0.30 mass% or less, Mo: 0 mass% or more, 0.30 mass% or less, Al: 0 mass% or more, 0.030 mass% or less, Ti: 0 mass% or more, 0.030 mass% or less, Nb: 0 mass% or more, 0.030 mass% or less, V: 0 mass% or more, 0.030 mass% or less, B: 0 mass% or more, 0.0030 mass% or less, N: More than 0 mass% and 0.0100 mass% or less.
[0021] With regard to the lower limit of the content of an element, "more than 0 mass%" generally means that the presence of the element is unavoidable and therefore the content cannot be made 0 mass%, and does not mean that the element is intentionally added. On the other hand, "0 mass% or more" means that intentional addition is not essential (although it may be added intentionally if desired), and that the element is not generally managed as an unavoidable impurity, and a content of 0 mass% or close to 0 mass% can be relatively easily achieved.
[0022] Each element will be described in detail below.
[0023] C: More than 0 mass%, 0.025 mass% or less C is an element that controls the balance between strength and ductility of steel materials, and the lower the C content, the lower the strength and the higher the ductility. However, in the normal steel manufacturing process, it is difficult to reduce the C content to zero even by vacuum degassing or other processes, so the lower limit is more than 0 mass%. C is usually contained as an impurity at about 0.001 to 0.010 mass%. If the C content is too high, the grain size of ferrite, a ferromagnetic material, becomes small, and the crystal grain boundaries become obstacles to magnetic domain wall motion, deteriorating the magnetic properties of soft magnetic parts obtained by cold forging and magnetic annealing the soft magnetic steel wire. If the C content is even higher, the ferrite area ratio decreases significantly and cementite precipitation is promoted. Since cementite hinders magnetic domain wall motion, the magnetic properties of the soft magnetic parts are further deteriorated, and since cementite becomes the starting point of cracks, cold forgeability is reduced. Taking these into consideration, the upper limit of the C content is set to 0.025 mass%. The C content is preferably 0.020 mass% or less, and more preferably 0.018 mass% or less. Note that, as long as the C content is within the above range, C may be intentionally added.
[0024] Si: 0 mass% or more, 2.00 mass% or less Si may be used as a deoxidizer during melting. In addition, Si has the effect of improving the magnetic properties of soft magnetic components. Si may be added to effectively exert these effects. However, since Si is not an essential element for obtaining the soft magnetic steel wire according to the present embodiment, it does not have to be intentionally added. Therefore, the lower limit of the Si content is 0 mass%. If Si is contained in excess, the cold forgeability of the soft magnetic steel wire and the magnetic properties of the soft magnetic parts obtained by cold forging and magnetic annealing the soft magnetic steel wire are deteriorated. For this reason, the upper limit of the Si content is set to 2.00 mass%. The Si content is preferably 1.00 mass% or less, more preferably 0.50 mass% or less, and further preferably 0.30 mass% or less.
[0025] Mn: 0.10 mass% or more, 0.50 mass% or less Mn effectively acts as a deoxidizer. Furthermore, Mn combines with S contained in the steel material and disperses finely in the steel as MnS precipitates, functioning as a chip breaker for chips generated during cutting. Therefore, Mn contributes to improving machinability. Furthermore, if there is a shortage of Mn, S combines with Fe to generate FeS, which deteriorates the magnetic properties of the soft magnetic parts. Taking these factors into consideration, the Mn content is set to 0.10 mass% or more. The Mn content is preferably 0.15 mass% or more, and more preferably 0.20 mass% or more. If the Mn content is too high, the cold forgeability of the soft magnetic steel wire and the magnetic properties of the soft magnetic part obtained by cold forging and magnetic annealing the soft magnetic steel wire deteriorate, so the Mn content is set to 0.50 mass% or less. The Mn content is preferably 0.45 mass% or less, more preferably 0.40 mass% or less, and further preferably less than 0.34 mass%.
[0026] P: More than 0% by mass, 0.050% by mass or less P is an element that causes grain boundary segregation in steel material and deteriorates both the cold forgeability of the soft magnetic steel wire and the magnetic properties of the soft magnetic parts obtained by cold forging and magnetic annealing the soft magnetic steel wire, and is an unavoidable impurity. Therefore, the P content is restricted to 0.050 mass% or less to improve the magnetic properties and cold forgeability. The P content is preferably 0.045 mass% or less, and more preferably 0.040 mass% or less. The smaller the P content, the better, but it is usually contained at about 0.005 mass %.
[0027] S: More than 0% by mass, 0.050% by mass or less S is an element that causes grain boundary segregation in steel material and deteriorates both the cold forgeability of the soft magnetic steel wire and the magnetic properties of the soft magnetic parts obtained by cold forging and magnetic annealing the soft magnetic steel wire, and is an unavoidable impurity. Therefore, the amount of S is restricted to 0.050 mass% or less to improve the cold forgeability of the soft magnetic steel wire and the magnetic properties of the soft magnetic parts. The amount of S is preferably 0.040 mass% or less, and more preferably 0.035 mass% or less. The smaller the S content, the more preferable, but it is usually contained in the range of about 0.001 to 0.010 mass %.
[0028] Cu: 0 mass% or more, 0.30 mass% or less Cu is an element that improves corrosion resistance. Cu may be added to effectively exert the above effect. On the other hand, Cu is not an essential element for obtaining the desired characteristics of the soft magnetic steel wire according to this embodiment, and therefore does not have to be intentionally added. Therefore, the lower limit of the Cu amount is 0 mass%. When Cu is intentionally added, the Cu amount is preferably 0.03 mass% or more, and more preferably 0.05 mass% or more. If Cu is contained in excess, the magnetic moment of the Fe matrix decreases, and the soft magnetic part does not obtain sufficient magnetic properties. For this reason, the Cu content is set to 0.30 mass% or less. The Cu content is preferably 0.25 mass% or less, more preferably 0.20 mass% or less, and even more preferably 0.10 mass% or less.
[0029] Ni: 0 mass% or more, 0.30 mass% or less Ni is an element that improves corrosion resistance. Ni may be added to effectively exert the above-mentioned effect. On the other hand, Ni is not an essential element for obtaining the desired characteristics of the soft magnetic steel wire according to this embodiment, and therefore does not have to be intentionally added. Therefore, the lower limit of the Ni amount is 0 mass%. When Ni is intentionally added, the Ni amount is preferably 0.03 mass% or more, and more preferably 0.05 mass% or more. If Ni is contained in excess, the magnetic moment of the Fe matrix decreases, and sufficient magnetic properties of the soft magnetic part cannot be obtained. For this reason, the Ni content is set to 0.30 mass% or less. The Ni content is preferably 0.25 mass% or less, more preferably 0.20 mass% or less, and even more preferably 0.10 mass% or less.
[0030] Cr: 0 mass% or more, 0.30 mass% or less Cr is an element that improves corrosion resistance. Cr may be added to effectively exert the above-mentioned effect. On the other hand, Cr is not an essential element for obtaining the desired characteristics of the soft magnetic steel wire according to the present embodiment, and therefore does not have to be intentionally added. Therefore, the lower limit of the Cr amount is 0 mass%. When Cr is intentionally added, the Cr amount is preferably 0.03 mass% or more, and more preferably 0.05 mass% or more. If Cr is contained in excess, the magnetic moment of the Fe matrix decreases, and the soft magnetic part does not obtain sufficient magnetic properties. For this reason, the Cr content is set to 0.30 mass% or less. The Cr content is preferably 0.25 mass% or less, more preferably 0.20 mass% or less, and even more preferably 0.10 mass% or less.
[0031] Mo: 0 mass% or more, 0.30 mass% or less Mo is an element that improves corrosion resistance. Mo may be added to effectively exert this effect. On the other hand, Mo is not an essential element for obtaining the desired characteristics of the soft magnetic steel wire according to this embodiment, and therefore does not have to be intentionally added. Therefore, the lower limit of the Mo amount is 0 mass %. When Mo is intentionally added, the Mo amount is preferably 0.01 mass % or more. If Mo is contained in excess, the magnetic moment of the Fe matrix decreases, and the magnetic properties of the soft magnetic part deteriorate. For this reason, the Mo content is set to 0.30 mass% or less. The Mo content is preferably 0.25 mass% or less, more preferably 0.20 mass% or less, and even more preferably 0.10 mass% or less.
[0032] Al: 0 mass% or more, 0.030 mass% or less Al is a nitride-forming element, and by forming nitrides and reducing the amount of solute N, it is effective in improving the magnetic properties of soft magnetic parts and improving cold forgeability by suppressing strain aging. Al may be added to effectively exert these effects. On the other hand, since Al is not an essential element for obtaining the desired properties of the soft magnetic steel wire according to the present embodiment, it is not necessary to intentionally add it. Therefore, the lower limit of the Al amount is 0 mass%. When Al is intentionally added, the Al amount is preferably 0.0001 mass% or more, more preferably 0.0005 mass% or more. If Al is added in excess, the magnetic moment of the Fe parent phase is reduced, and the magnetic properties of the soft magnetic parts are reduced. Furthermore, AlN formed by combining Al with N in the steel material acts as a pinning particle that suppresses grain growth in the magnetic annealing process. As a result, the grain boundaries that are an obstacle to the movement of the Al domain wall increase, and the magnetic properties of the soft magnetic parts are reduced. In addition, the cold forgeability is also deteriorated due to the refinement of ferrite grains accompanying the suppression of grain growth. Therefore, the Al content is set to 0.030 mass% or less. In order to provide soft magnetic parts with better magnetic properties, the Al content is preferably 0.025 mass% or less, more preferably 0.020 mass% or less, and even more preferably less than 0.010 mass%.
[0033] Ti: 0 mass% or more, 0.030 mass% or less, Nb: 0 mass% or more, 0.030 mass% or less, V: 0 mass% or more, 0.030 mass% or less Ti, V, and Nb are carbide-forming elements, and by forming carbides and reducing solute C, they are effective in improving the magnetic properties of soft magnetic parts and improving cold forgeability by suppressing strain aging. In order to effectively exert these effects, one or more elements selected from the group consisting of Ti, V, and Nb may be added. On the other hand, Ti, V, and Nb are not essential elements for obtaining the desired properties of the soft magnetic steel wire according to this embodiment, so they do not need to be intentionally added. Therefore, the lower limits of the Ti content, V content, and Nb content are all 0 mass%.
[0034] When one or more of Ti, V and Nb are intentionally added, the content of each element is preferably 0.005 mass % or more. If Ti, V, and Nb are each contained in excess, the pinning effect of carbides inhibits grain growth, and the magnetic properties of the soft magnetic component deteriorate. Therefore, the Ti content, V content, and Nb content are each set to 0.030 mass% or less. Each of the Ti content, V content, and Nb content is preferably set to 0.025 mass% or less, and more preferably set to 0.020 mass% or less. The total amount of Ti, V and Nb is preferably 0 mass % or more and 0.060 mass % or less.
[0035] B: 0 mass% or more, 0.0030 mass% or less B is an element that combines with N in the steel material to form BN and reduces solute N, thereby improving the magnetic properties of soft magnetic parts and improving the cold forgeability of soft magnetic steel wire by suppressing strain aging. B may be added to effectively exert this effect. On the other hand, B is not an essential element for obtaining the soft magnetic steel wire according to the present embodiment, so it does not have to be added intentionally. Therefore, the lower limit of the B content is 0 mass%. When B is intentionally added, the B content is preferably 0.0005 mass% or more. If B is contained in excess, compounds such as Fe2B will precipitate at the grain boundaries, degrading the magnetic properties of the soft magnetic parts. For this reason, the B content is set to 0.0030 mass% or less. The B content is preferably 0.0025 mass% or less, and more preferably 0.0020 mass% or less.
[0036] N: More than 0 mass%, 0.0100 mass% or less N is an unavoidable impurity that dissolves in steel and causes a strain aging effect, deteriorating cold forgeability. In addition, if the N content is high, nitrides are formed and act as pinning particles that suppress grain growth in the magnetic annealing process. This increases the number of grain boundaries that hinder domain wall movement, and reduces the magnetic properties of the soft magnetic parts. For this reason, the upper limit of the N content is set to 0.0100 mass%. The N content is preferably 0.0080 mass% or less, and more preferably 0.0070 mass% or less. The smaller the N content, the more preferable, but it is usually contained at about 0.0010 mass %.
[0037] The basic components are as described above, and in one preferred embodiment, the balance is iron and inevitable impurities. Examples of inevitable impurities include elements (e.g., O, As, Sb, Ca, H, etc.) that are introduced due to the conditions of raw materials, materials, manufacturing facilities, etc. In addition, for example, there are elements such as P and S, whose content is usually the lower the better and therefore they are unavoidable impurities, but whose composition ranges are separately specified as above. Therefore, in this specification, when referring to "unavoidable impurities" that make up the balance, it is a concept that excludes elements whose composition ranges are separately specified.
[0038] 2.Metal structure The metal structure of the soft magnetic steel wire according to the embodiment contains a ferrite phase at an area ratio of 95.0% or more, the grain size number of the ferrite phase is 7.0 or less, and the grain boundary ratio containing cementite with an equivalent circle diameter of 0.1 μm or more and 3 μm or less is 6.8% or more.
[0039] (The area ratio of the ferrite phase is 95.0% or more.) In order to increase the magnetic moment of the Fe matrix, it is necessary to include a large amount of ferrite phase, which is a ferromagnetic material, in the metal structure of the soft magnetic steel wire. Furthermore, if the amount of ferrite phase is small, cold forgeability deteriorates. For this reason, the metal structure of the soft magnetic steel wire according to the embodiment of the present invention includes a ratio of ferrite phase of 95.0% or more in area ratio. The area ratio of the ferrite phase is preferably 98.0% or more.
[0040] Furthermore, if the area ratio of the ferrite phase is low, the metal structure of the soft magnetic wire / bar before wiredrawing becomes non-uniform, and the roundness of the soft magnetic steel wire after wiredrawing tends to deteriorate (i.e., the roundness value increases). By making the area ratio of the ferrite phase 95.0% or more, preferably 98.0% or more, the roundness of the soft magnetic steel wire can be improved (i.e., the roundness value can be reduced). As described later, the roundness of the soft magnetic steel wire affects the dimensional accuracy of parts obtained by cold forging, so good roundness is preferable.
[0041] In this specification, the "area ratio of the ferrite phase" may be abbreviated to "ferrite area ratio".
[0042] The ferrite area ratio is determined by the following procedure. A soft magnetic steel wire of an appropriate length is taken and embedded in resin so that the cross section can be observed. The surface of the cross section is mirror-polished, and then the metal structure is revealed by nital etching. The D / 4 position (D: wire diameter of the soft magnetic steel wire) on the cross section is observed with an optical microscope at 50 to 100 times magnification, and a rectangular field of view of 700 to 1200 μm x 1000 to 1500 μm is photographed. On the photograph, 10 equally spaced lines parallel to the long side and 10 equally spaced lines parallel to the short side are drawn in a grid pattern to form 100 intersections. Of the 100 intersections, the number of intersections located on ferrite (number of ferrite points) is counted, and the ferrite area ratio (%) is calculated from the occupancy rate of the intersections by ferrite. This operation is performed at three different D / 4 positions, and the arithmetic average of the ferrite area ratios determined at each D / 4 position is defined as the ferrite area ratio of the soft magnetic steel wire.
[0043] When the cross-sectional shape of the soft magnetic steel wire is a square or regular hexagon, the wire diameter D is the average value of multiple diagonals drawn on the cross-sectional shape (square or regular hexagon) of the steel wire. When the cross-section is a square, the average value of two diagonals is taken as the wire diameter D, and when the cross-section is a regular hexagon, the average value of three diagonals is taken as the wire diameter D. Then, the same operation as in the method for calculating the "ferrite area ratio" described above is performed at three different D / 4 positions, and the arithmetic average of the ferrite area ratios calculated at each D / 4 position is taken as the ferrite area ratio of the soft magnetic steel wire.
[0044] (Ferrite phase grain size number is 7.0 or less) If the crystal grain size of the ferrite phase in the metal structure of the soft magnetic steel wire is small, the strength of the soft magnetic steel wire tends to increase and the cold forgeability of the soft magnetic steel wire decreases. In addition, if the crystal grain size of the ferrite phase is small, the crystal grain growth during magnetic annealing after cold forging becomes insufficient, and the crystal grain size of the ferrite phase after magnetic annealing becomes small. If the crystal grain size is small, the number of crystal grain boundaries increases, and the crystal grain boundaries may hinder domain wall motion and deteriorate the magnetic properties. In other words, if the crystal grain size of the ferrite phase in the metal structure of the soft magnetic steel wire is small, the magnetic properties of the soft magnetic part obtained by cold forging and magnetic annealing the soft magnetic steel wire may deteriorate. Therefore, by increasing the crystal grain size of the ferrite phase in the metal structure of the soft magnetic steel wire, the cold forgeability of the soft magnetic steel wire can be improved, and the magnetic properties of the soft magnetic part can be improved.
[0045] Therefore, in the soft magnetic steel wire according to the embodiment of the present invention, the grain size number of the ferrite phase is controlled to 7.0 or less. The grain size number of the ferrite phase is preferably 6.5 or less. From the viewpoint of improving the magnetic properties of the soft magnetic parts obtained by cold forging and magnetic annealing the soft magnetic steel wire, the larger the grain size of the soft magnetic steel wire, the more preferable it is, so the lower limit of the grain size number of the ferrite phase is not limited. However, since it is difficult to obtain a very large grain size in industrial production, the ferrite grain size number may be -3.0 or more. In addition, if the grains of the ferrite phase become extremely coarse, there is a possibility that the ductility and toughness will decrease and the cold forgeability will decrease, so the ferrite grain size number is preferably -3.0 or more, more preferably -1.0 or more, and even more preferably 0.0 or more.
[0046] In this specification, the "grain size number of the ferrite phase" may be abbreviated to "ferrite grain size."
[0047] The ferrite grain size is determined by the following procedure. A soft magnetic steel wire of an appropriate length is taken and embedded in resin so that the cross section can be observed. The surface of the cross section is mirror-polished, and then the metal structure is revealed by nital etching. The D / 4 position (D: wire diameter of the soft magnetic steel wire) on the cross section is observed with an optical microscope at 50-100x magnification, and a field of view of 700-1200μm x 1000-1500μm is photographed. The photograph is used to determine the grain size number in accordance with JIS G0551:2020. This operation is carried out at three different D / 4 positions, and the arithmetic average of the grain size numbers determined at each D / 4 position is defined as the grain size number of the soft magnetic steel wire. When pearlite is present in the metal structure, the layered ferrite in the pearlite is excluded from the grain size number of the ferrite phase.
[0048] When the cross-sectional shape of the soft magnetic steel wire is a square or regular hexagon, as described above, the average value of multiple diagonals drawn on the cross-sectional shape (square or regular hexagon) of the steel wire is taken as the wire diameter D, and the same operation as that for determining the "ferrite grain size" described above is performed at three different D / 4 positions, and the arithmetic average of the grain size numbers determined at each D / 4 position is taken as the grain size number of the soft magnetic steel wire.
[0049] The grain size number may be determined using an optical microscope photograph taken when determining the ferrite area ratio.
[0050] (The rate of grain boundaries containing cementite with a circular equivalent diameter of 0.1 μm to 3 μm is 6.8% or more) The present inventors have made the following findings. If there is a large amount of C dissolved in the Fe matrix, it causes strain aging, which increases the deformation resistance and reduces cold forgeability. In order to reduce the amount of C dissolved, it is effective to precipitate a large amount of cementite (cementite at grain boundaries or within grains). On the other hand, coarse cementite is likely to become the starting point of cracks during cold forging, which can cause a decrease in cold forgeability. Furthermore, cementite within grains traps dislocations and causes an increase in dislocations, which may lead to an increase in deformation resistance due to work hardening.
[0051] Based on these findings, it was concluded that in order to improve cold forgeability, it is effective to precipitate a large amount of fine cementite at the grain boundaries. However, in pure iron with a low C content, the amount of cementite precipitated is very small, making it difficult to quantitatively evaluate the amount of cementite at the grain boundaries. Therefore, as a simple method, the amount of cementite at the grain boundaries was evaluated by measuring the amount of grain boundaries containing cementite. The larger the amount of grain boundaries containing cementite (sometimes referred to as "high rate of grain boundaries containing cementite" in this specification), the larger the amount of cementite at the grain boundaries.
[0052] The cementite to be measured is limited to those with an equivalent circle diameter of 0.1 μm or more and 3 μm or less. Cementite with an equivalent circle diameter of less than 0.1 μm is excluded from the measurement because it has a low effect of reducing strain aging and its small grain size makes it difficult to observe with a microscope such as an SEM. Cementite with an equivalent circle diameter of more than 3 μm is excluded from the measurement because it hardly exists in pure iron-based soft magnetic steel wire.
[0053] In order to improve cold forgeability, it is effective to increase the amount of cementite at the grain boundaries. Increasing the amount of cementite at the grain boundaries means increasing the grain boundary ratio containing cementite. As a result of investigations from the viewpoint of improving cold forgeability, the lower limit of the grain boundary ratio containing cementite having a circle equivalent diameter of 0.1 μm or more and 3 μm or less was set to 6.8%. The grain boundary ratio is preferably 6.9% or more. The upper limit of the grain boundary ratio is not particularly limited, but is usually 40% or less because it is a pure iron system with an extremely small amount of C.
[0054] In this specification, the "grain boundary ratio containing cementite having an equivalent circle diameter of 0.1 μm or more and 3 μm or less" may be abbreviated as the "grain boundary ratio containing cementite" or the "grain boundary ratio".
[0055] The rate of grain boundaries containing cementite is determined by the following procedure. Measurement equipment: Commercially available optical microscope or scanning electron microscope Observation area: Rectangular shape of 234μm×176μm (×500x) Observation position: Observe so that the center position of the cross section of the soft magnetic steel wire roughly coincides with the center of the observation area (the intersection of the diagonals of the rectangular observation area). Identification of cementite phase: Divide the above observation area into nine sections (3 x 3), and observe each section using a secondary electron image (2000x to 5000x magnification). In the secondary electron image, the white phase is judged to be the cementite phase. Target cementite: Cementite with a circle equivalent diameter of 0.1 μm or more and 3 μm or less is specified. Cementite with a circle equivalent diameter of less than 0.1 μm or more than 3 μm is excluded.
[0056] The obtained image is analyzed, and the number of grain boundaries is counted, treating them as lines. When grain boundaries intersect, the line segments between the intersections are considered to be one grain boundary. The total number of grain boundaries present within the observation range (number of grain boundaries within the observation range) and the number of grain boundaries that contain the target cementite (number of grain boundaries containing cementite) are calculated. The rate of grain boundaries containing cementite is calculated by the following formula. Percentage of grain boundaries containing cementite (%) = (number of grain boundaries containing cementite) / (number of grain boundaries within observation range) × 100
[0057] 3. Relationship between roundness and wire diameter of soft magnetic steel wire The dimensional accuracy of a soft magnetic part obtained by cold forging a soft magnetic steel wire is closely related to the roundness of the soft magnetic steel wire. The present inventors have conducted extensive research and found that the dimensional accuracy of a soft magnetic part obtained by cold forging at a high processing rate is high when a soft magnetic steel wire is used in which the roundness of the soft magnetic steel wire and an index calculated from the wire diameter satisfy a predetermined relationship. Specifically, it is preferable that the roundness and wire diameter of the soft magnetic steel wire satisfy the following formula (1), whereby a soft magnetic steel wire suitable for manufacturing soft magnetic parts with high dimensional accuracy can be obtained. R≦0.100-(20-D) / 500 (1) Here, R is the roundness of the soft magnetic steel wire, and D (mm) is the wire diameter of the soft magnetic steel wire. In this specification, for the sake of simplicity, the right side of formula (1) (i.e., "0.100-(20-D) / 500") may be conveniently replaced with "X." Equation (1) can be rewritten as the following equation (1)' using X. R≦X (1)'
[0058] More preferably, the roundness R of the soft magnetic steel wire satisfies the following formula (2): This provides a soft magnetic steel wire that is particularly suitable for manufacturing parts with high dimensional accuracy. R≦(0.100-(20-D) / 500)-0.035 (2) Incidentally, formula (2) can be rewritten as the following formula (2)' using X. R≦X-0.035 (2)'
[0059] In the soft magnetic steel wire according to the embodiment of the present invention, the cross-sectional shape of a cross section perpendicular to the longitudinal direction (transverse cross section) may be, for example, circular, or may be another cross-sectional shape (square or regular hexagon).
[0060] In this specification, the wire diameter D of a soft magnetic steel wire is the equivalent circle diameter obtained from the cross-sectional area (transverse section) of the steel wire when the cross section is circular. The equivalent circle diameter can be obtained, for example, by image analysis of a stereomicroscope photograph of the cross section of the steel wire using image analysis software (e.g., Image J).
[0061] The roundness R of a soft magnetic steel wire (the difference between the maximum and minimum diameters of the steel wire divided by 2) can be automatically calculated using a commercially available image measuring device (for example, the IM-7000 (manufactured by Keyence)).
[0062] When the cross-sectional shape of a soft magnetic steel wire is a square or a regular hexagon, the roundness R and wire diameter D shall be as follows. The circularity R of a square and a regular hexagon is calculated using the diagonals. Draw diagonals on each figure (two for a square, three for a regular hexagon), and measure the longest diagonal by L. max (mm), the shortest diagonal is L min Let us assume that L max and L min Substitute this into the following formula (3) to calculate the roundness R. Roundness R(mm)=(L max -L min ) / twenty three)
[0063] In addition, the wire diameter D is the average value of multiple diagonals drawn on the cross-sectional shape (square or regular hexagon) of the steel wire's transverse section. In the case of a square cross section, the average value of two diagonals is taken as the wire diameter D, and in the case of a regular hexagon cross section, the average value of three diagonals is taken as the wire diameter D.
[0064] The wire diameter D of the soft magnetic steel wire is not particularly limited, but is, for example, 0.5 mm to 50 mm.
[0065] 4. Vickers hardness The processing strain imparted to the soft magnetic steel wire by wire drawing reduces the cold forgeability of the soft magnetic steel wire. Vickers hardness is a physical index related to the amount of processing strain. In the case of a pure iron-based soft magnetic steel wire such as the soft magnetic steel wire according to the embodiment of the present invention, the Vickers hardness is preferably 200HV or less, and good cold forgeability can be obtained. The Vickers hardness is more preferably 185HV or less, and further preferably 170HV or less.
[0066] The Vickers hardness is determined by the following procedure. A soft magnetic steel wire of an appropriate length is taken and embedded in resin so that the cross section can be observed. After mirror polishing the surface of the cross section, the Vickers hardness is measured at the center of the cross section. In accordance with JIS Z2244:2020, the distance between adjacent indentations is measured three times with a load of 1 kgf (9.81 N) and a distance of at least 3d (d: diagonal length of the indentation), and the arithmetic average is the Vickers hardness of the soft magnetic steel wire.
[0067] 5. Half-width of the diffraction peak of the ferrite phase The present inventors have found that the half-width of the diffraction peak of the ferrite phase in an X-ray diffraction pattern is suitable as another index of the processing strain imparted to a soft magnetic steel wire by wire drawing. The greater the processing strain, the larger the half-width of the diffraction peak of the ferrite phase becomes. In the case of a pure iron-based soft magnetic steel wire according to an embodiment of the present invention, in an X-ray diffraction pattern measured using Cr-Kα radiation as an X-ray source, the half-width of the diffraction peak (peak in the range of 2θ=148° to 165°) of the (211) plane of the ferrite phase is preferably 1.75° or less, and good cold forgeability can be obtained. The half-width is more preferably 1.70° or less.
[0068] The smaller the half-value width, the better the cold forgeability, so there is no lower limit for the half-value width. When wire drawing is performed to obtain a soft magnetic steel wire with high roundness (for example, roundness of 0.100 mm or less), the half-value width is usually 0.30° or more.
[0069] The half-value width of the diffraction peak of the ferrite phase is determined by the following procedure. A soft magnetic steel wire of an appropriate length is taken and embedded in resin so that the cross section can be observed. The surface of the cross section is mirror-polished, and then the metal structure is revealed by nital etching. An X-ray diffraction pattern is obtained at the D / 4 position (D: wire diameter of the soft magnetic steel wire) on the cross section using a micro X-ray diffraction device (e.g., PSPC micro X-ray stress measurement device, manufactured by Rigaku Corporation) with Cr-Kα radiation. In the obtained X-ray diffraction pattern, the peak present at 148° to 165° is assigned to the X-ray diffraction peak from the (211) plane of the ferrite phase, and its half-value width (°) is measured. This operation is performed at three different D / 4 positions, and the arithmetic average of the half-widths determined at the respective D / 4 positions is regarded as the half-width of the X-ray diffraction pattern of the soft magnetic steel wire.
[0070] When the cross-sectional shape of the soft magnetic steel wire is a square or regular hexagon, as described above, the average value of multiple diagonals drawn on the cross-sectional shape (square or regular hexagon) of the cross-section of the steel wire is taken as the wire diameter D, and then the same operation as in the method for determining the "half-width of the diffraction peak of the ferrite phase" described above is performed at three different D / 4 positions, and the arithmetic average of the half-widths determined at each D / 4 position is taken as the half-width of the X-ray diffraction pattern of the soft magnetic steel wire.
[0071] 6.Magnetic properties The soft magnetic steel wire according to the embodiment of the present invention can be used to manufacture soft magnetic parts having good coercive force by performing magnetic annealing after part processing, and is therefore suitable as a material for manufacturing soft magnetic parts such as iron cores and covers used in solenoids, relays, solenoid valves, etc.
[0072] 7. Manufacturing method A method for producing a soft magnetic steel wire according to an embodiment of the present invention includes the steps of: [1] A process of heating a cast material having a predetermined chemical composition to 950 ° C to 1250 ° C, hot rolling or hot forging at 900 ° C to 1100 ° C, and then cooling to 500 ° C at an average cooling rate of 0.1 ° C / sec to 10 ° C / sec to obtain a wire rod or a steel bar; [2] A process of drawing the wire or steel bar at a wire drawing reduction rate of 5 to 40%; [3] After the wire drawing process, a heat treatment process is performed at a temperature of 150°C or more and 500°C or less for 15 minutes or more and 10 hours or less. Includes.
[0073] [1] A process in which a cast material having a specified chemical composition is heated to 950°C to 1250°C, hot-rolled or hot-forged at 900°C to 1100°C, and then cooled to 500°C at an average cooling rate of 0.1°C / s to 10°C / s to obtain wire rod or steel bar. Steelmaking raw materials are melted to satisfy a predetermined chemical composition, and the molten steel obtained is cast to obtain a cast material. Casting may be performed by batch processing to obtain an ingot, or by continuous casting. The cast material may be subjected to processing such as surface grinding as necessary. The obtained cast material is heated to 950℃ to 1250℃, and then hot-rolled or hot-forged at 900℃ to 1100℃, processed into the desired shape, and then cooled to 500℃ at an average cooling rate of 0.1℃ / sec to 10℃ / sec. Cooling at temperatures below 500℃ may be performed at any rate. By producing wire rods and steel bars under these conditions, the soft magnetic steel wire finally obtained can satisfy the desired ferrite area ratio, ferrite grain size, and grain boundary ratio including cementite. Note that if the grain size of the wire rods and steel bars after rolling is large, the grain size of the steel wire after wire drawing tends to be large, and the ferrite area ratio of the wire rods and steel bars after rolling does not change even after wire drawing.
[0074] [2] A process in which wire or bar steel having a specified chemical composition is drawn at a wire drawing reduction rate of 5 to 40%. A wire or bar having a specified chemical composition is drawn at a wire drawing reduction rate of 5 to 40%. The wire drawing area reduction rate is set to 5% or more, and preferably 6% or more. When the wire drawing area reduction rate is high, the amount of processing strain inside the soft magnetic steel wire increases, and the cold forgeability of the soft magnetic steel wire decreases. Furthermore, when the wire drawing area reduction rate is excessive, the roundness of the soft magnetic steel wire may deteriorate. Therefore, the upper limit of the wire drawing area reduction rate is set to 40%. The wire drawing area reduction rate is preferably 35% or less, more preferably 32% or less, and further preferably 30% or less.
[0075] The "drawing reduction rate" is the reduction rate of area obtained from the cross-sectional area of the wire or steel bar before the drawing process and the cross-sectional area after the drawing process. When multiple drawing passes are performed, the drawing reduction rate is obtained from the cross-sectional area before the multiple drawing passes are performed and the cross-sectional area after all the drawing passes are completed. Furthermore, when annealing is performed in the middle of multiple wiredrawing passes, the wiredrawing reduction rate is determined from the cross-sectional area immediately after annealing and the cross-sectional area after all wiredrawing passes performed after annealing are completed. The cross-sectional area of the wire or steel bar can be determined, for example, by analyzing a stereomicroscope photograph of the cross section using image analysis software (for example, Image J).
[0076] Since the wire drawing process can contribute to improving the roundness of the soft magnetic steel wire, by carrying out an appropriate wire drawing process, it is possible to manufacture a soft magnetic steel wire suitable for manufacturing soft magnetic parts with high dimensional accuracy.
[0077] [3] After the wire drawing process, a heat treatment process is performed in which the wire is kept at a heat treatment temperature of 150°C or higher and 500°C or lower for 15 minutes or more and 10 hours or less. In order to control the grain size of cementite at the grain boundaries, it is necessary to perform heat treatment (low-temperature heat treatment) after wire drawing. If the heat treatment temperature is too low, the precipitation of cementite at the grain boundaries becomes insufficient, and the size cannot be ensured sufficiently. Therefore, the lower limit of the heat treatment temperature is set to 150°C. The heat treatment temperature is preferably 170°C or higher, and more preferably 180°C or higher.
[0078] If the heat treatment temperature is too high, the cementite at the grain boundaries and the cementite within the grains will coarsen, and the grain boundary ratio containing cementite with a circle equivalent diameter of 0.1 μm to 3 μm will decrease (i.e., cold forgeability will decrease). In addition, the energy consumption during heat treatment will increase. Therefore, the upper limit of the heat treatment temperature is set to 500°C. The heat treatment temperature is preferably 475°C or less, more preferably 450°C or less.
[0079] If the time for holding the heat treatment temperature set within the range of 150°C or more and 500°C or less (sometimes referred to as "heat treatment time") is short, the precipitation of cementite at the grain boundaries becomes insufficient. Therefore, the lower limit of the heat treatment time is set to 15 minutes. The heat treatment time is preferably 20 minutes or more, more preferably 30 minutes or more. If the heat treatment time is long, the cementite at the grain boundaries and the cementite within the grains become coarse, and the grain boundary ratio containing cementite with a circle equivalent diameter of 0.1 μm to 3 μm or less decreases (cold forgeability decreases). Furthermore, the cold forgeability decreases due to oxidation promotion / surface property deterioration. In addition, power consumption also increases. Therefore, the upper limit of the heat treatment time is set to 10 hours. The heat treatment time is preferably 6 hours or less, more preferably 3 hours or less.
[0080] The rate of temperature rise to the heat treatment temperature is not particularly limited, but from the viewpoint of productivity, a rate of temperature rise of 30° C. / hour or more is preferable. The rate of cooling after the heat treatment is not particularly limited, but from the viewpoint of productivity, a rate of 100° C. / hour or more is sufficient, and air cooling or rapid cooling is preferable. The atmosphere during the heat treatment is not particularly limited and may be any atmosphere since the heat treatment temperature is relatively low and oxidation of the steel wire surface does not progress significantly. From the viewpoint of cost, the heat treatment in air is preferable.
[0081] A person skilled in the art who has come into contact with the manufacturing method of the soft magnetic steel wire according to the embodiment of the present invention described above may be able to obtain, through trial and error, the soft magnetic steel wire according to the present invention by a manufacturing method different from the above-mentioned manufacturing method. EXAMPLES
[0082] Tests were conducted on soft magnetic steel wire samples made of the chemical composition shown in Table 1. The content of each element shown in Table 1 is the result of processing the measurement results of each element, with less than the significant figure (number of decimal places) of the content specified for each element, in accordance with JIS Z 8401:2019. The contents of Ti, Nb, V, and B were below the detection limit (i.e., the measured value was 0.000%).
[0083] Steelmaking raw materials having the chemical composition shown in Table 1 were melted by a normal melting method, and the resulting molten steel was cast to obtain a cast material. The resulting cast material was heated to 950°C to 1250°C, hot-rolled at 900°C to 1100°C, and cooled to 500°C at an average cooling rate of 0.1°C / s to 10°C / s to obtain a rolled steel bar material of φ20 to φ25. After removing the oxide film from the rolled steel bar material, cold wire drawing was performed using a laboratory wire drawing machine at the wire drawing reduction rate shown in Table 2 to obtain a steel wire with a wire diameter shown in Table 2. The wire drawing reduction rate in Table 2 was calculated from the cross-sectional area of the wire or steel bar before wire drawing and the cross-sectional area after wire drawing. Thereafter, the steel wire was subjected to low-temperature annealing under the heat treatment conditions shown in Table 2 to obtain a soft magnetic steel wire for measurement (test material). The cross-section of the test material (cross-section perpendicular to the axis of the measurement sample) had a circular cross-sectional shape. The following measurements were carried out using the obtained test materials.
[0084] (Wire diameter D of soft magnetic steel wire (test material)) The equivalent circle diameter calculated from the cross-sectional area of the test material was defined as wire diameter D (mm). For each of the test materials of Samples No. 1 to 7, the wire diameter D of the test material is shown in the column of "Wire diameter D after wiredrawing" in Table 2.
[0085] (Circularity R of soft magnetic steel wire (test material)) Three measurement samples with lengths of 10 mm to 30 mm were prepared from each of the test materials of Samples No. 1 to 7. The roundness R of each measurement sample was automatically measured using an image measuring device (Image Dimension Measuring Device IM-7000 (manufactured by Keyence)). The arithmetic mean of the roundness obtained from the three measurement samples was calculated and recorded in the "Roundness R" column of Table 3.
[0086] Since the roundness depends on the wire diameter of the soft magnetic steel wire, the pass / fail judgment was made using the relational expressions (formulas (1) and (2)) between the roundness R (mm) and the wire diameter D (mm). R≦0.100-(20-D) / 500 (1) R≦(0.100-(20-D) / 500)-0.035 (2) Here, let "X=100-(20-D) / 500", and the right-hand side of equation (1) be regarded as X, and the right-hand side of equation (2) be regarded as X-0.035. Whether or not formula (1) and formula (2) were satisfied was judged and recorded in Table 5. If the formula was satisfied, a "○" was marked, and if not, an "×" was marked.
[0087] Here, the roundness of the soft magnetic steel wire before cold forging is evaluated. The dimensional accuracy after cold forging is strongly influenced by the roundness before cold forging. Therefore, the roundness of the test material evaluated in this test is used as an index for estimating the dimensional accuracy of the forged product after cold forging of the soft magnetic steel wire.
[0088] (Ferrite area ratio) Measurement samples with lengths of 10 mm to 30 mm were taken from each of the test materials of Samples No. 1 to 7, and embedded in resin so that the cross section could be observed. The surface of the cross section was mirror-polished by Emily polishing and / or diamond buff polishing, and then the metal structure was revealed by nital etching. The following measurements were performed at the D / 4 position (D: wire diameter of the soft magnetic steel wire) in the circular cross section as the measurement position. The measurements were performed at three different D / 4 positions. Each of the three D / 4 positions was observed with an optical microscope at 50 to 100 times magnification, and three fields of view (one field of view is a rectangular shape of 700 to 1200 μm × 1000 to 1500 μm) were photographed. Ten lines at equal intervals parallel to the long sides and ten lines at equal intervals parallel to the short sides were drawn in a grid pattern on the photographed images, forming 100 intersections. Of the 100 intersections, the number of intersections located on ferrite (number of ferrite points) was counted, and the ferrite area ratio was calculated from the ferrite intersection occupancy rate. The same procedure was performed for each of the three photographs (three fields of view). The ferrite area ratios (%) calculated from each field of view were arithmetically averaged and are shown in Table 3.
[0089] (Ferrite grain size) The grain size number was determined according to JIS G0551:2020 using optical microscope photographs (three visual fields) taken for measuring the ferrite area ratio. The grain size numbers calculated from the photographs of each visual field were arithmetically averaged and listed in Table 3. Note that pearlite was not present in the test materials of Samples No. 1 to 7.
[0090] (Grain boundary ratio containing cementite) The ratio of grain boundaries containing cementite was determined in the following manner. Measurement equipment: JSM-7001F field emission scanning electron microscope (manufactured by JEOL Ltd.) Observation area: 234μm×176μm (×500x) Observation position: The center position of the cross section of the soft magnetic steel wire was adjusted to roughly coincide with the center of the observation area (the intersection of the diagonals of the rectangular observation area). Identification of the cementite phase: The above observation area was divided into nine sections (3 x 3), and each section was observed using secondary electron images (2000x to 5000x magnification). In the secondary electron images, the white phase was determined to be the cementite phase. Target cementite: Cementite with a circle equivalent diameter of 0.1 μm or more and 3 μm or less was specified. Cementite with a circle equivalent diameter of less than 0.1 μm or more than 3 μm was excluded.
[0091] The obtained images were analyzed, and the number of grain boundaries was counted, regarding them as lines. When grain boundaries intersected, the line segment between the intersections was considered to be one grain boundary. The total number of grain boundaries present within the observation range (number of grain boundaries within the observation range) and the number of grain boundaries that contained the target cementite (number of grain boundaries containing cementite) were calculated. The rate of grain boundaries containing cementite was calculated from the following formula. Percentage of grain boundaries containing cementite (%) = (number of grain boundaries containing cementite) / (number of grain boundaries within observation range) × 100 The calculated grain boundary ratios containing cementite are shown in the "Grain boundary ratio" column of Table 3.
[0092] (Method for measuring the half-width of the X-ray diffraction peak of the (211) plane of the ferrite phase) The half-width of the X-ray diffraction peak of the (211) plane of the ferrite phase is determined as follows. Measurement samples measuring 10 mm to 30 mm in length were taken from each of the test materials of Samples No. 1 to 7, and embedded in resin so that the cross section could be observed. The surface of the cross section was mirror-polished by Emily polishing and / or diamond buff polishing. The following measurements were performed at the D / 4 position (D: wire diameter of the soft magnetic steel wire) on the circular cross section. The measurements were performed at three different D / 4 positions.
[0093] X-ray diffraction patterns were obtained from each of the three D / 4 positions using a PSPC micro X-ray stress measurement device (Rigaku Corporation). The measurement conditions were as follows: target: Cr, X-ray source: Cr-Kα ray, acceleration voltage: 40 kV, acceleration current: 40 mA, collimator: φ1.0 mm, measurement time: 100 seconds. In the obtained X-ray diffraction pattern, the peaks present at 148° to 165° were assigned to the X-ray diffraction peaks from the (211) plane of the ferrite phase, and their half-widths (°) were measured. The half-widths obtained from three X-ray diffraction measurements were arithmetically averaged and shown in Table 3.
[0094] (Vickers hardness) Measurement samples with lengths of 10 mm to 30 mm were taken from each of the test materials of Samples No. 1 to 7, and embedded in resin so that the cross section could be observed. The surface of the cross section was mirror-polished by Emily polishing and / or diamond buff polishing. Vickers hardness was measured at the center position of the cross section. In accordance with JIS Z2244:2020, the distance between adjacent indentations was measured three times with a distance of 3d or more (d: diagonal length of the indentation), and the arithmetic average was calculated and listed in Table 4. The load was 1 kgf (9.81 N). Vickers hardness (average value) is rated as "unacceptable" for over 200HV, "passable" for 200HV or less, "good" for 185HV or less, and "excellent" for 170HV or less.
[0095] (Evaluation of cold forgeability: deformation resistance and the presence or absence of cracks) Three cold forged test pieces (cylindrical test pieces) were taken from each of the test materials of Samples No. 1 to 7. The test materials were cut to lengths of 25 to 30 mm, and then machined to obtain cylindrical test pieces with a diameter / height ratio of 1.5. For example, the dimensions of the cylindrical test piece of Sample No. 1 (diameter of test material: 19.4 mm) were φ18 mm×27 mmL, and the dimensions of the cylindrical test piece of Sample No. 7 (diameter of test material: 15.8 mm) were φ14 mm×21 mmL. The surface roughness of the cylindrical test specimen was a medium finish (Ra = 3.2 μm to 6.3 μm) on the bottom surface (corresponding to the cross section) and a fine finish (Ra = 0.4 μm to 1.6 μm) on the side surface.
[0096] A cold forging test (compression test) was carried out using cylindrical test pieces under the following conditions. Compression direction: Height direction of the cylindrical specimen (longitudinal direction of the cylindrical specimen) Compression temperature: Room temperature Strain rate: approx. 5 / sec to 10 / sec Compression rate: 90% Number of tests for each sample: 3 A compression ratio of 90% means that the cylindrical specimen is compressed in a direction parallel to its height until it is reduced to 10% of its original height (e.g., 3 mm for a cylindrical specimen 30 mm high).
[0097] Deformation resistance The deformation resistance of the test material when compressed by 85% was calculated from the data of the cold forging test. The deformation resistance of the three test materials was calculated as an arithmetic average and is shown in the "Deformation Resistance" column of Table 4. The deformation resistance (average value) is rated as "unacceptable" for over 900 MPa, "passable" for 900 MPa or less, and "good" for 890 MPa or less.
[0098] ·Cracks or not The entire circumference of the side of the test pieces (referred to as "cold forged materials") after the cold forging test (three pieces for each of the test pieces of Samples No. 1 to 7) was observed with a stereomicroscope (magnification: 20 times) to confirm the presence or absence of cracks. Note that since cracks mainly occurred on the side of the test pieces and hardly occurred on the bottom surface (corresponding to the cross section), the bottom surface was not observed. The cracks observable under the stereomicroscope at the above magnification had a maximum dimension of about 0.2 mm or more. The number (range 0 to 3) of cold-forged materials in which cracks were confirmed (i.e., cold-forged materials in which one or more cracks were present) was counted and recorded in the "Number of confirmed cracks" column in Table 4. Cold-forged materials in which cracks were confirmed were rated as "unacceptable" when the number was 1 to 3, and rated as "acceptable" when the number was 0.
[0099] (Evaluation of magnetic properties: coercive force) For the evaluation of magnetic properties, the above cold forged materials were subjected to magnetic annealing and then the coercive force was measured. Magnetic annealing was performed under general magnetic annealing conditions for pure iron-based soft magnetic materials (specifically, the temperature was raised to 850°C in 2 to 4 hours, then the material was held at 850°C for 3 hours, cooled to 400°C or less at a cooling rate of 100°C / hour, and then allowed to cool). The magnetic annealing atmosphere was a hydrogen atmosphere. An automatic coercivity meter Hc (K-HC1000, manufactured by Tohoku Special Steel Co., Ltd.) was used for the measurements. When measuring the coercivity of the soft magnetic parts, a magnetic field was applied so that the compression direction (axial direction of the cold forged material) and the magnetization direction were perpendicular. The coercivity was measured once. Coercive force of over 50A / m is rated as "unacceptable" and 50A / m or less is rated as "acceptable."
[0100] Table 1 shows the chemical composition of the steel material, Table 2 shows the manufacturing conditions of the test materials for each sample, and Tables 3 to 5 show the measurement results and evaluation results. In Table 2, the mark (-) indicates that the process was not performed. In other words, in the case of sample No. 2, the heat treatment after wire drawing was not performed. In Tables 2 and 3, underlined values indicate values that are outside the range of the embodiment of the present invention. However, please note that "-" is not underlined even if the value is outside the range of the embodiment of the present invention.
[0101] [Table 1]
[0102] [Table 2]
[0103] [Table 3]
[0104] [Table 4]
[0105] [Table 5]
[0106] Consider the results in Table 3. The test materials of Samples No. 1 and 4 to 7 are examples that satisfy all of the requirements of the embodiment of the present invention.
[0107] The test material of Sample No. 2 was not subjected to heat treatment after wire drawing, and therefore the precipitation of cementite at the grain boundaries could not be sufficiently controlled, resulting in high deformation resistance. Although the test material of Sample No. 3 was subjected to heat treatment after wire drawing, the heat treatment temperature was low, so that the precipitation of cementite at the grain boundaries could not be sufficiently controlled, resulting in high deformation resistance.
[0108] In addition, when comparing the test material of sample No. 6 with the test material of sample No. 7, the test material of sample No. 7 had a high wire drawing area reduction rate, so the processing strain increased and the deformation resistance was relatively high. In addition, although the roundness of the test material of sample No. 7 met the acceptance criteria of the embodiment of the present invention (satisfying formula (1)), it did not meet the more preferable criteria (satisfying formula (2)).
Claims
1. C: more than 0 mass%, 0.025 mass% or less, Si: 0 mass% or more, 2.00 mass% or less, Mn: 0.10% by mass or more, 0.50% by mass or less, P: more than 0 mass%, 0.050 mass% or less, S: more than 0 mass%, 0.050 mass% or less, Cu: 0 mass% or more, 0.30 mass% or less, Ni: 0 mass% or more, 0.30 mass% or less, Cr: 0 mass% or more, 0.30 mass% or less, Mo: 0% by mass or more and 0.30% by mass or less, Al: 0% by mass or more, 0.030% by mass or less, Ti: 0% by mass or more, 0.030% by mass or less, Nb: 0 mass% or more, 0.030 mass% or less, V: 0% by mass or more, 0.030% by mass or less, B: 0% by mass or more, 0.0030% by mass or less, N: more than 0 mass% and 0.0100 mass% or less; The balance is Fe and unavoidable impurities, The area ratio of the ferrite phase is 95.0% or more, The grain size number of the ferrite phase is 7.0 or less, A soft magnetic steel wire having a grain boundary ratio of 6.8% or more, the grain boundary ratio including cementite having an equivalent circle diameter of 0.1 μm or more and 3 μm or less.
2. 2. The soft magnetic steel wire according to claim 1, wherein a roundness R (mm) and a wire diameter D (mm) satisfy the following formula (1): R≦0.100-(20-D) / 500 (1)
3. The soft magnetic steel wire according to claim 2 , further satisfying formula (2). R≦(0.100-(20-D) / 500)-0.035 (2)
4. 2. The soft magnetic steel wire according to claim 1, wherein in an X-ray diffraction pattern measured using Cr-Kα radiation as an X-ray source, the half-value width of a diffraction peak of a (211) plane of the ferrite phase is 1.75° or less.
5. A method for producing the soft magnetic steel wire according to any one of claims 1 to 4, comprising the steps of: A step of heating a cast material having the chemical composition according to claim 1 to 950°C to 1250°C, hot rolling or hot forging at 900°C to 1100°C, and then cooling to 500°C at an average cooling rate of 0.1°C / sec to 10°C / sec to obtain a wire rod or a steel bar; A step of drawing the obtained wire rod or steel bar at a wire drawing reduction rate of 5 to 40%; A method for producing a soft magnetic steel wire, comprising: after the wiredrawing step, a heat treatment step of holding the wire at a heat treatment temperature of 150°C or more and 500°C or less for 15 minutes or more and 10 hours or less.
Citation Information
Patent Citations
Soft magnetic low carbon steel having excellent machinability and magnetic property, production method therefor and method for producing soft magnetic low carbon steel parts obtained by using the same steel
JP2003055745A
Manufacturing method of soft magnetic steel component
JP2017128784A
Soft magnetic steel sheet
JP2018104789A
Soft magnetic wire material, soft magnetic steel bar and soft magnetic component
JP2023133104A
Soft magnetic steel and soft magnetic steel component including the same
JP2023148845A